Tiger eyes : a novel - Blume, Judy. (Scarsdale, N.Y. : Bradbury Press, 1981)
Resettled in the "Bomb City" with her mother and brother, Davey Wexler recovers from the shock of her father's death during a holdup of his 7-Eleven store in Atlantic City.
Notable/Best Books (A.L.A.).
School Library Journal.
Wilson's Junior High School.
7-9
Young Adult
Keywords: Death -- Fiction; Grief -- Fiction; Death -- Fiction; Grief -- Fiction